Physical, chemical and rheological investigation and optimization design of asphalt binders partially replaced by bio-based resins. (3rd October 2022) - Jiang, Xiuming; Li, Peilong; Ding, Zhan; Yue, Lei; Li, Huifeng; Bing, Hui; Zhang, Jing
Highlights: Improved high-temperature performance is observed in the bio-asphalt binders. BPF resins weaken the temperature and moisture susceptibility of asphalt binders. The aging process is accompanied by additional condensation of the BPF resin. It is suggested to quantify the aging behavior of bio-asphalt binders by SO. Indicators η 70, 10 ∗, BBS, penetration and δ 46, 10 are the most representative. Abstract: The utilization of bio-asphalt binders has become an active topic in highway engineering, whereas the challenges cannot be ignored in terms of high-temperature performance, aging, moisture and temperature susceptibility etc. A novel bio-asphalt binder was introduced in this investigation, in which traditional petroleum-based asphalt binders were partially replaced (10%, 20%, 30% and 50%) by bio-based phenol–formaldehyde (BPF) resins. This work aims to evaluate the feasibility and advantages of BPF resins as a potential alternative from a comprehensive perspective considering the properties of physics, chemistry and rheology. Multiple macro and micro test methods were conducted for performance evaluation, and principal component analysis (PCA) and hierarchical cluster analysis (HCA) were applied to reveal the similarities and correlations between their indicators. The results show that the heavy and elastic components in bio-asphalt binders was increased for the contribution of BPF resins. Hence, the deformation recovery ability and rutting resistance are improved at high temperatures, which is deserved despite the increase in the viscosity and construction temperature. Compared with the neat asphalt binder, more significant hydrophobicity and better adhesion properties were found in bio-asphalt binders. Noteworthy, the additional condensation reactions of BPF resins and the oxidation of asphalt binders occur simultaneously in the aging process, and the sulfoxide index was suggested to quantify the aging behavior. For the complicated evaluation indicators, four clusters with strong Pearson correlations were determined based on PCA and HCA, and the dosage of 30% for BPF resin was acceptable.